An Electrochemical Molecularly Imprinted Polymer Sensor for Rapid β-Lactoglobulin Detection - Wang, Bixuan; Hong, Jingyi; Liu, Chun; Zhu, Liying; Jiang, Ling (Sensors (Basel, Switzerland), 2021)
Facile detection of β-lactoglobulin is extraordinarily important for the management of the allergenic safety of cow’s milk and its dairy products. A sensitive electrochemical sensor based on a molecularly imprinted polymer-modified carbon electrode for the detection of β-lactoglobulin was successfully synthesized. This molecularly imprinted polymer was prepared using a hydrothermal method with choline chloride as a functional monomer, β-lactoglobulin as template molecule and ethylene glycol dimethacrylate as crosslinking agent. Then, the molecularly imprinted polymer was immobilized on polyethyleneimine (PEI)-reduced graphene oxide (rGO)-gold nanoclusters (Au-NCs) to improve the sensor’s selectivity for β-lactoglobulin. Under optimal experimental conditions, the designed sensor showed a good response to β-lactoglobulin, with a linear detection range between 10−9 and 10−4 mg/mL, and a detection limit of 10−9 mg/mL (S/N = 3). The developed electrochemical sensor showed a high correlation in the detection of β-lactoglobulin in four different milk samples from the market, indicating that the sensor can be used with actual sample.